Dipanggil untuk Bersekutu dan Memberitakan Injil: Sejarah Gerakan Injili di Indonesia Perhatian Khusus Kepada Persekutuan Injili Indonesia Tahun 1971 - Yusup Yusup (Veritas : Jurnal Teologi dan Pelayanan, 2025)
This study aims to trace the history of the evangelical movement in Indonesia and its development leading up to the formation of the Indonesian Evangelical Fellowship (PII) in 1971. This study employs a historical method, in which the heuristic process of data collection was conducted through document analysis, literature review, and interviews, which were subsequently selected, interpreted, and presented in the written report. The results reveal that three factors shaped the evangelical movement in Indonesia. In addition to two internal dynamics—namely, the entry of evangelical mission agencies into Indonesia and the polarization of the mission movement at the global level—the consolidation of the evangelical movement in Indonesia was also influenced by an external factor: the political dynamics in Indonesia following 1965.